A Randomized Controlled Trial of Interleukin-1 Receptor Antagonist in a Rabbit Model of Ascending Infection in Pregnancy. Issue 4 (2001) - McDuffie, Robert S.; Davies, Jill K.; Leslie, Kimberly K.; Lee, Scott; Sherman, Michael P.; Gibbs, Ronald S.
Abstract : Objective: To determinewhether treatment with interleukin-1 receptor antagonist (IL1-ra) would affect amniotic fluid concentrations of tumor necrosis factor alpha (TNF-α) and prostaglandins or clinical or microbiological outcomes in a model of ascending bacterial infection in pregnancy. Methods: Timed pregnant New Zealand white rabbits at 70% of gestation underwent endoscopic inoculation of the cervices with10 6 –10 7 cfu Escherichia coli . Animals were randomly assigned in a blinded manner to a 5-h intravenous infusion of human IL1-ra (10 mg/kg) or placebo beginning 1 – 2 h after inoculation. Blood was drawn fromthe does for assay of serum IL1-ra concentration before inoculation, at mid-infusion, after the infusion ended and at necropsy. At necropsy, temperature and cultures were taken, and aspirated amniotic fluid was pooled for assays of TNF-α, prostaglandin E 2 ( PGE 2 ) and IL1-ra. Results: Serum IL1-ra concentrations rose to a mean of 2 mg/ml at mid-infusion and fell markedly after the infusion to concentrations barely detectable at necropsy. Between the two groups, there were no significant differences in the rates of fever or positive cultures or in amniotic fluid concentrations of PGE 2 or TNF-α.One unique finding was the demonstration that administration of human IL1-ra to the does resulted inmeasurable concentrationsof human IL1-ra in the amniotic fluid. Conclusions: Treatment with an intravenous infusion of human IL1-ra after cervical inoculation with E. coli did not affect clinical or microbiological outcomes or amniotic fluid concentrations of TNF-α or PGE 2 . This experiment provides the first demonstration of passageof human IL1-ra from the maternal bloodstreamto the amniotic fluid.